Cholesterol Ester Storage Disease in Two Field Spaniels With Lysosomal Acid Lipase Deficiency - Syrjä, Pernilla; Ylenius, Mathilda M. H.; Kråkström, Matilda; Dickens, Alex M.; Rautala, Elina; Huupponen, Anna; Eriksson, Anders; Viitanen, Sanna J. (John Wiley & Sons, 2026)
Cholesterol ester storage disease (CESD) is a rare genetic lysosomal storage disorder resulting from lower lysosomal acid lipase (LAL) activity. LAL is an essential enzyme required in intracellular lipid metabolism, and deficiency results in disability to properly break down and utilize lipids and in the accumulation of especially cholesterol esters in many organs such as the liver, spleen, and bone marrow. This case report describes clinical findings, LAL activity measurement, blood and liver tissue lipidomic changes, as well as pathological findings in two unrelated Field Spaniels with LAL deficiency and CESD.